2018
DOI: 10.1002/marc.201800377
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin‐Caged Polyphosphazenes with a Visible‐Light Driven On‐Demand Degradation

Abstract: Polymers that, upon photochemical activation with visible light, undergo rapid degradation to small molecules are described. Through functionalization of a polyphosphazene backbone with pendant coumarin groups sensitive to light, polymers which are stable in the dark could be prepared. Upon irradiation, cleavage of the coumarin moieties exposes carboxylic acid moieties along the polymer backbone. The subsequent macromolecular photoacid is found to catalyze the rapid hydrolytic degradation of the polyphosphazen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…[2] Metallopolymers can offer unique properties and an umber of supramolecular systemsh ave been developed based on dynamic ligand-metali nteractions. Examples include the incorporation of coumarin [10] or o-nitrobenzyl [11] groupsi nto polymericm aterials [12, 10] to achieve selective photodegradation.While materials responsive to UV-light have long been established,t here has been ar ecent shift in the field towards the use of photochemical processes, which respond in the visible and NIR region [13, 11a] due to the poor penetration of high-energyU V-lighta sw ell as its incompatibility with biological environments. [6] Also an umber of ruthenium-containingm etallopolymers have been reported,w ith ap articular focus on their use as stimuli-responsivepolymers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Metallopolymers can offer unique properties and an umber of supramolecular systemsh ave been developed based on dynamic ligand-metali nteractions. Examples include the incorporation of coumarin [10] or o-nitrobenzyl [11] groupsi nto polymericm aterials [12, 10] to achieve selective photodegradation.While materials responsive to UV-light have long been established,t here has been ar ecent shift in the field towards the use of photochemical processes, which respond in the visible and NIR region [13, 11a] due to the poor penetration of high-energyU V-lighta sw ell as its incompatibility with biological environments. [6] Also an umber of ruthenium-containingm etallopolymers have been reported,w ith ap articular focus on their use as stimuli-responsivepolymers.…”
mentioning
confidence: 99%
“…[7] Meanwhile, photocleavable polymers,t hat is polymers whichc leave or degrade in response to irradiation with certain wavelengths of light have been recently developed. Examples include the incorporation of coumarin [10] or o-nitrobenzyl [11] groupsi nto polymericm aterials [12, 10] to achieve selective photodegradation. Examples include the incorporation of coumarin [10] or o-nitrobenzyl [11] groupsi nto polymericm aterials [12, 10] to achieve selective photodegradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers which can be cleaved or undergo backbone disassembly upon response to light in a spatiotemporal manner are of interest as positive photoresists or in controlled release applications. In this context, our group has recently reported polyphosphazenes which undergo rapid degradation to small molecules upon photochemical activation with light in the visible region . This works on the basis of an hydrolytically instable poly(glycine)phosphazene backbone, in which the acid groups are caged (protected) by photochemically labile coumarin moieties (Figureà).…”
Section: Photoresponsive Polymersmentioning
confidence: 99%
“…Another distinct advantage of coumarin derivatives is the tunability of absorption wavelength by molecular design ( λ max from 310 nm to 490 nm), thus providing broader compatibility with light wavelength [ 26 , 29 ]. Reports have shown that the electron donating diethylamino substituents at the 7-position allows photochemical activity in the visible region, further allowing cleavage of the coumarin moieties from the polyphosphazene backbone upon visible light irradiation [ 30 ]. Xu et al also reported a propesticide with 7-diethylamino substituted coumarin as a photocage for the release of insecticidal ingredients upon blue light or sunlight [ 31 ].…”
Section: Introductionmentioning
confidence: 99%